A Study to Assess the Effectiveness of Video-assisted Teaching Programme on Knowledge Regarding Prevention and First Aid Management of Snakebite Among Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) Workers in Selected Areas at Wayanad - Ruby V.P.; Ramudevi C.; Jismy Ouseph; Jwala P.P.; Kavyasree C.; Krishna Shibu; Layasree P.S.; Laya Thomas (International Journal of Emergency and Trauma Nursing and Practices, 2023)
This study aimed to assess the impact of a video-assisted instructional program on the awareness of snake bite prevention and first aid practices among MGNREGS workers in Meppadi Panchayath, Wayanad. Using a quasi-experimental one-group pre-test post-test research approach, the study included 60 participants selected through convenient sampling. The participants' demographics revealed a varied distribution, with the majority falling within the 36–45 year age bracket (35%) and having an educational background of 8–12th standard (86.6%). The study found that none of the participants had received previous training regarding snake bite prevention. The video-assisted teaching program significantly improved participants' knowledge levels, shifting from an average level (64%) to a good level (87%). The statistical analysis indicated a significant association between pre-test knowledge scores and the level of education (p value = 0.03 < 0.05), highlighting the effectiveness of the program. However, no significant associations were observed with other demographic variables, including age, religion, and working experience. In conclusion, the video-assisted teaching program proved to be effective in enhancing knowledge about the prevention and first aid management of snake bites among MGNREGS workers. The findings underscore the importance of tailored educational interventions, especially considering the significant impact on individuals with varying levels of education.
Keywords: Knowledge; MGNREGS; effectiveness; first aid management; prevention; snakebite; video-assisted teaching program